THE USE OF ELECTROPHORESIS FOR THE ADDITIONAL ESTIMATION OF NEW ISOLATES OF FUNGUS PLEUROTUS OSTREATUS (JACQ.: FR.) KUMMER - Дорошкевич, Н. В. (Scientific Progress & Innovations, 2013)
In this work the additional estimation of new isolates of the P. ostreatus fungus by their tolerance to electrophoresis was made. The ability of fungus to produce extracellular proteins in cultural liquid (CL) is a response reaction on carbonaceous materials of nutrient medium was determined. Relationship between quality of protein fractions on EFS of lyophilizes CL after cultivation at wort medium with the ability of fungus to accumulate biomass on liquid wort and them yield fructification on sunflower husk was established. The electrophoresis method may be used in future as the additional for characteristic of new isolates of the P. ostreatus fungus.